Agora Studio - Traveling Exposition 1975. - Centro di Arte y Communication, Buenos Aires; Estudio Actual, Carracas; Museo de Arte Contemporaneo, São Paulo (Maastricht : Agora Studio, 1975)
Van Beveren, Peter ; Cardena, Michel ; Carrión, Ulises ; Cavellini Guglielmo, Achille ; Albrecht D. ; Druks, Michael ; Francis, Filip ; Gibbs, Michael ; Van Geluwen, Johan ; Groh, Klaus ; Krijn Herrebout, Manja ; Deleu, Luc ; Mrroquin, Raul ; Mesterom, Harry ; Nakajima, Yoshio ; Nannucci, Maurizio ; Schumans, Marjo ; Seur, Han ; Schill, Ruedi ; De Smet, Yves ; Summers, Rod ; Urban, Nikolaus ; Vercammen, Wout ; Wessels, Dick
Agora Studio - Traveling Exposition 1975, Agora Studio, Maastricht, autumn 1975 ; Centro di Arte y Communication, Buenos Aires ; Estudio Actual, Carracas ; Museo de Arte Contemporaneo, São Paulo
boek